Broad vs narrow brand positioning: effects on competitive brand performance. (4th February 2022) - Olsen, Lars Erling; Meling Samuelsen, Bendik; Pappas, Ioannis; Warlop, Luk
Abstract : Purpose: Brand managers can choose among two fundamentally different brand positioning strategies. One is a broad brand strategy, focusing on many favorable brand associations. The other is a narrow brand strategy, focusing on just a few and thus more mentally accessible associations. Building on associative memory theory, this paper aims to examine which of these brand positioning strategies performs better under dynamic market conditions. Design/methodology/approach: Three experiments test the effect of brand positioning strategy on memory accessibility and competitive brand performance. Study 1 tests how brand strategy (broad vs narrow) affects defensive brand performance. Study 2 tests how broad vs narrow brands perform differently in a brand extension scenario (offensive brand performance). Study 3 uses real brands and situation-based attributes as stimuli in a defensive scenario. Findings: The results show that a narrow brand positioning strategy leads to a competitive advantage. Narrow brands with fewer and more accessible associations resist new competitors more easily and have higher brand extension acceptance than do broad brands. Research limitations/implications: The study shows how to use accessibility as evidence of associative strength and test how accessibility influences competitive brand performance in a controlled experimental context. Practical implications: Brand managers would benefit from a narrow brand positioning strategy in accordance with the unique selling proposition (USP) school of thought used by many marketing practitioners. Originality/value: The paper demonstrates that narrow brand positioning performs better than broad brand positioning in dynamic markets, and to the knowledge is the first to do so.